Antagonism of clonidine injected intracerebroventricularly in different models of salt intake - Sato, M. A. [UNESP]; Yada, M. M. [UNESP]; Renzi, A. [UNESP]; Camargo, L. A.A. [UNESP]; Saad, W. A. [UNESP]; Menani, J. V. [UNESP]; De-Luca, L. A. [UNESP] (My University, 1996)
Clonidine, an α2-adrenergic agonist, injected into the brain inhibits salt intake of animals treated by the diuretic model of sodium depletion. In the present study, we address the question of whether central injection of clinidine also inhibits salt intake in amimals deprived of water or in the need-free state. Saline or clonidine (30 nmol) was injected into the anterior third ventricle of 24-h sodium-depleted (furosemide + removal of ambient sodium), of 24-h water-deprived and of normovolemic (need-free state) adult male rats. Clonidine injected intracerebroventricularly (icv) inhibited the 1.5% NaCl intake for 120 min by 50 to 90% in every model tested. Therefore, different models of salt intake are inhibited by icv injection of clinidine. Idazoxan, and α2-adrenergic antagonist, injected icv at a dose of 160 nmol, inhibited the effect of clonidine only in the furosemide + removal of ambient sodium model of salt intake. This indicates that the antagonism of this effect by idazoxan is dependent on the body fluid/sodium status of the animal.
Keywords: adrenoceptors; dehydration; idazoxan; sodium intake